Indirect Spectrophotometric Determination of Niclosamide in Pharmaceutical Preparations - Nabeel S. Othman; Saad H. Sultan (College of Education for Pure Sciences, 2018)
A simple and sensitive indirect spectrophotometric method is developed for the determination of niclosamide in pharmaceutical preparations. The method is based on the oxidation of reduced form of niclosamide with iron ( III ) in acidic medium, then the subsequent reaction of iron ( II ) with 1,10- phenanthroline to produce a ferroin complex which is water - soluble , stable (using EDTA solution improve the stability of the complex) , and has a maximum absorption at 510 nm against the reagent blank with a molar absorptivity of 2.19×104 l.mol-1.cm-1 . Beer,s law is valid over the concentration range of 2.5 to 225 μg/10 ml. The relative error is in between - 1.80 and +1.50 % and the relative standard deviation from ± 0.89 to ± 2.07 % depending on the concentration of niclosamide . The proposed method has been applied successfully to determine niclosamide in pharmaceutical preparations.